2017
DOI: 10.1186/s13058-017-0913-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum thymidine kinase 1 activity as a pharmacodynamic marker of cyclin-dependent kinase 4/6 inhibition in patients with early-stage breast cancer receiving neoadjuvant palbociclib

Abstract: BackgroundThymidine kinase 1 (TK1) is a cell cycle-regulated enzyme with peak expression in the S phase during DNA synthesis, and it is an attractive biomarker of cell proliferation. Serum TK1 activity has demonstrated prognostic value in patients with early-stage breast cancer. Because cyclin-dependent kinase 4/6 (CDK4/6) inhibitors prevent G1/S transition, we hypothesized that serum TK1 could be a biomarker for CDK4/6 inhibitors. We examined the drug-induced change in serum TK1 as well as its correlation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 34 publications
(48 reference statements)
3
45
1
1
Order By: Relevance
“…Abemaciclib was FDA approved in September 2017 in combination with fulvestrant as a second-line treatment after the phase II MONARCH-2 trial (Sledge et al 2017) and as monotherapy after progression on endocrine therapy and chemotherapy from the phase II MONARCH-1 trial . It was later approved in February 2018 in combination with letrozole as first-line treatment based on results from the phase III MONARCH-3 trial (Goetz et al 2017).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Abemaciclib was FDA approved in September 2017 in combination with fulvestrant as a second-line treatment after the phase II MONARCH-2 trial (Sledge et al 2017) and as monotherapy after progression on endocrine therapy and chemotherapy from the phase II MONARCH-1 trial . It was later approved in February 2018 in combination with letrozole as first-line treatment based on results from the phase III MONARCH-3 trial (Goetz et al 2017).…”
Section: Figurementioning
confidence: 99%
“…One possible explanation may be that p19 INK4D is transcribed downstream of E2F activity due to non-functional Rb, and further E2F targets, cyclin D3 and CDKN2D were also identified in the patients with refractory tumours. The same group subsequently identified that another E2F target, thymidine kinase 1, may be useful as a pharmacodynamic biomarker to monitor the initial patient response to CDK4/6 inhibitors (Bagegni et al 2017).…”
Section: Endocrine-related Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…GNAS is observed in both tumor and normal samples, as well as in the hemimethylation study for breast cancer cell lines [8]. MEIS1 is also a hub gene that interacts with genes like KMT2A [39] and TK1 [40]. While these genes are not hemimethylated in our samples, they are known to be associated with cancer.…”
Section: Resultsmentioning
confidence: 75%
“…TK-1 overexpression is similarly observed in cancer models, 30,31 and its association with the Ki67 proliferation index has been demonstrated in various cancers. [32][33][34] Interestingly, AAA [ 18 F]FLT uptake was observed after 14 days of AngII infusion, when aneurysms expand, but this effect was weaker after 28 days, when the growth phase begins to plateau, suggesting decreased cell proliferation in late-stage AAA. This supports the idea of early-stage cellular remodeling leading to late-stage replicative senescence, which has been reported in end-stage human AAA samples.…”
Section: Discussionmentioning
confidence: 99%